MiR-218 affects hypertrophic differentiation of human mesenchymal stromal cells during chondrogenesis via targeting RUNX2, MEF2C, and COL10A1 - Melnik, Svitlana; Gabler, Jessica; Dreher, Simon I.; Hecht, Nicole; Hofmann, Nina; Großner, Tobias; Richter, Wiltrud (Stem cell research & therapy, 2020)
Human mesenchymal stromal cells (MSC) hold hopes for cartilage regenerative therapy due to their chondrogenic differentiation potential. However, undesirable occurrence of calcification after ectopic transplantation, known as hypertrophic degeneration, remains the major obstacle limiting application of MSC in cartilage tissue regeneration approaches. There is growing evidence that microRNAs (miRs) play essential roles in post-transcriptional regulation of hypertrophic differentiation during chondrogenesis. Aim of the study was to identify new miR candidates involved in repression of hypertrophy-related targets.
Gesehen am 18.01.2021